Family Harmony On Juvenile Deliquency - Mbooh, Yaret Munda; Manurung, Imelda F. E.; Manafe, Rizky Pradita (Journal of Health and Behavioral Science, 2025)
Adolescence is a transitional phase that is vulnerable to various forms ofdeviant behavior, one of which is juvenile delinquency. The family environment, asthe first environment known by children, plays a vital role in the formation ofadolescent personality. This study aims to determine the effect of family harmony onjuvenile delinquency in class X students at SMA Negeri 1 Lobalain. This study useda quantitative method, and the sampling technique used purposive sampling. Thisresearch instrument uses a Likert scale to measure family harmony and juveniledelinquency variables. The validity test was carried out using the Pearson ProductMoment correlation of each statement item in the questionnaire. The results of simpleregression analysis show that there is a significant influence between family harmonyon juvenile delinquency. This study emphasizes the importance of the family's role inpreventing juvenile delinquency.